In search of cinema : writings on international film art - Cardullo, Bert (McGill-Queen's University Press, 2004)
Chronicles the vitality of international film art in the last two decades. At a time when the movie review has degenerated into mere publicity for Hollywood pictures and film scholarship has become entangled in its own pseudo-scientific discourse, Bert Cardullo reclaims the territory of a certain type of film critic, somewhere between a reviewer-journalist and a scholar-theorist. With elegance, clarity, and rigour, he offers close readings of individual films to show how moviemakers use the resources of the medium to pursue complex, significant human goals. The essays collected here reflect the spectacular rise of Iranian cinema in recent years as well as the strong contributions of contemporary filmmakers from countries such as Belgium, Canada, China, Israel, Lebanon, Scotland, and Spain. The book covers the best recent films from major film-producing nations like the United States, France, and Italy and includes retrospective pieces on the careers of Ingmar Bergman and Woody Allen as well as several essays on the interrelationship between film form, or film genres, and drama and the novel, the two forms from which the cinema continues to draw a wealth of its material.
Keywords: Motion pictures.; Motion pictures -- Reviews.; Motion pictures -- History.; Cinéma -- Comptes rendus.; Cinéma -- Histoire.; Cinéma.; JUVENILE NONFICTION -- Performing Arts -- Film.; PERFORMING ARTS -- Film & Video -- History & Criticism.; Motion pictures; Film; Critique cinématographique.; Reviews; History; Films.